Kunst in Arbeit: Künstlerisches Arbeiten zwischen Praxis und Phänomen - Schürkmann, Christiane (transcript, 2017)
Art is beautiful, but requires a lot of work. This ethnographic study shows exactly how artistic work is created in practice.